Daily deep acting toward coworkers: An examination of day-specific antecedents and consequences - Hadar Nesher Shoshan; Laura Venz (Journal of Organizational Behavior, 2021)
Emotional labor in coworker interactions is a prevalent phenomenon in everyday work. Yet, it is largely unknown whether it is also a relevant phenomenon, that is, whether emotional labor toward coworkers matters for employee daily work life. Addressing this question, we investigate day-specific antecedents and consequences of coworker-directed emotional labor, especially deep acting. We hypothesized that deep acting toward coworkers will be rewarded by coworkers providing emotional and task support and that this coworker support, in turn, will predict enhanced positive affect at the end of work. Further, we suggest that high morning positive affect enables employees to deep act toward their coworkers in the first place. During a 10-workday diary study, 102 employees answered surveys on 6180.167emdays. Multilevel path analysis showed that morning positive affect predicted daily deep acting toward coworkers, which was positively related to emotional (but not task) support from coworkers. Emotional (but not task) support predicted higher end-of-work positive affect and mediated the relationship between deep acting and end-of-work positive affect. Findings highlight the importance of studying deep acting toward coworkers as part of a positive dynamic process that employees can experience at work. Our results bring along vital theoretical and practical implications.
Keywords: 650; deep acting; diary study; emotional labor toward coworkers; social support; state positive affect